Students’ Satisfaction with the University of Cape Coast Residential and Academic Experiences: Students’ Satisfaction with the University of Cape Coast Residential and Academic Experiences (Journal of Educational Management, 2021)
The purpose of the study is to explore students’ satisfaction with the University of Cape Coast experience. The study adopted a sequential explanatory mixed-method design and used current students as the population of the study. A sample size of 420 students was used for the study. The study used questionnaires and focus group interview guides to obtain data from participants. The study used descriptive statistics and a thematic analysis approach to analyse the data obtained. The study revealed that students are less satisfied with residential services and attributed this to irregular water supply, unsanitary toilet and urinal facilities, congestion in student rooms. Furthermore, the study showed that students were less satisfied with some academic services. The study recommended that the leadership of departments, faculties and colleges need to review their curriculum with the approval of the Academic Board to enhance students’ practical experiences in their academic programmes.
Keywords: academic; resident; higher education; service; student satisfaction